Measuring the Geographical Displacement and Diffusion of Benefit Effects of Crime Prevention Activity - Bowers, Kate (Journal of quantitative criminology, 2003)
The displacement of crime is an important criminological phenomenon. However, while there has been theoretical discussion of this issue in the research literature, there has been little in the way of either standardized empirical work that investigates the incidence of displacement or in the development of techniques that can be used to measure it. In the current paper we discuss a new technique, the weighted displacement quotient (WDQ), that was developed to measure the geographical displacement of crime. A critical feature of the rationale is that displacement can only be attributed to crime prevention activity if crime is reduced in the target area considered. Thus, the WDQ not only measures what occurs in a buffer (displacement) zone but also relates changes in this area to those in the target area. Part of the appeal of the measure is that it can be used either with aggregate or disaggregate crime data and for any geographical boundary selected, provided the appropriate data are available. In addition to detecting displacement, when detailed data are available, the technique can also be used to identify where the effect was most prominent. The WDQ can equally be used to measure the diffusion of benefit of any crime prevention activity. A series of examples are presented for illustration purposes.